Effect of Pscyrotroph Bacteria on Physical and Chemical Properties of Traditional White and Ultrafilteration Cheese - EZZATI, R.; DEZYANI*, M.; ALLAH MIRZAEI†, H. (Asian Journal of Chemistry, 2009)
The dominant factor of stored raw milk in low temperature arePscyrotroph bacteria and these bacteria as referred as to microorganismsthat can survive and grow at 7 ºC or lower. Pscyrotroph bacteria is notheat resistance and pasteurization destroy them, but their proteolyticand lypolytic enzymes are heat resistance. These enzymes save theiractivities in pasteurization temperature and also UHT processing. Inthis study, effect of Pscyrotroph bacteria on physical and chemical propertieson ultrafilteration and white cheese was investigated. The resultsshowed that number of Pscyrotroph bacteria on white and ultrafilterationcheese was significant, so with increasing Pscyrotroph bacteria the drymatter per cent, per cent of fat and firmness of texture was reduced. Inspite of this, moisture of curd and softness of cheese texture increasedby multiplying Pscyrotroph bacteria. These changes in the ultrafilterationcheese were more than white cheese.